2011
DOI: 10.1002/adfm.201101173
|View full text |Cite
|
Sign up to set email alerts
|

Active Enzyme Nanocoatings Affect Settlement of Balanus amphitrite Barnacle Cyprids

Abstract: Balanus amphitrite cyprids produce complex adhesive substances that enable their attachment to surfaces and impart a strong detachment resistance from most immersed substrata. The colonization of man‐made structures by barnacle cyprids and other marine organisms is a troublesome and costly phenomenon, for which controlling strategies are actively sought. In this work, we expand previous investigations about the susceptibility of cyprid adhesives to unpurified proteases in solution by evaluating the interplay b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…It causes many negative consequences on marine industry and maritime activities, such as increased frictional resistance and fuel consumption of ships, accelerated corrosion of metal and blocked seawater pipelines in near‐sea energy infrastructures . The global ban of effective but highly toxic tributyl‐tin (TBT) based self‐polishing coatings urges the development of ecofriendly antifouling systems, including silicone‐based fouling release coatings (FRC), degradable polymers with dynamic surfaces, polymethacrylate bearing ferrocenyl groups, amphiphilic copolymers, liquid‐infused slippery surfaces, surface‐deforming materials, enzyme containing coatings, and so on. Among them, silicone‐based FRCs with excellent fouling release ability have gained considerable attention because it is environment‐friendly and has drag reducing ability …”
Section: Introductionmentioning
confidence: 99%
“…It causes many negative consequences on marine industry and maritime activities, such as increased frictional resistance and fuel consumption of ships, accelerated corrosion of metal and blocked seawater pipelines in near‐sea energy infrastructures . The global ban of effective but highly toxic tributyl‐tin (TBT) based self‐polishing coatings urges the development of ecofriendly antifouling systems, including silicone‐based fouling release coatings (FRC), degradable polymers with dynamic surfaces, polymethacrylate bearing ferrocenyl groups, amphiphilic copolymers, liquid‐infused slippery surfaces, surface‐deforming materials, enzyme containing coatings, and so on. Among them, silicone‐based FRCs with excellent fouling release ability have gained considerable attention because it is environment‐friendly and has drag reducing ability …”
Section: Introductionmentioning
confidence: 99%
“…The immobilization of subtilisin A onto highly swelling, poly(ethylene-alt-maleic anhydride) copolymer films was found to be advantageous because it permitted higher enzyme loading and activity compared with enzyme immobilization onto the compact hydrophobic poly(octadecene-alt-maleic anhydride) copolymer films [19]. Studies evaluating the effects of immobilized subtilisin A on the initial steps of settlement and adhesion of marine bacteria, green algae spores, diatoms, and larger marine invertebrates revealed that the adhesion strength decreased in the presence of the active enzyme [18,20]. In addition, a higher antifouling efficacy was observed for the immobilized enzyme when compared with similar amounts of free enzyme indicating the importance of enzyme localization at the cell-coating interface [18].…”
Section: Enzymes For Antifoulingmentioning
confidence: 96%
“…Enzymes can also remove the proteinaceous cues necessary for larval attachment (Dobretsov et al 2007). For instance, proteolytic enzymes can cleave proteinaceous adhesives and reduce adhesion strength in a variety of fouling organisms including bacteria (Friedrichs et al 2012), diatoms (Pettitt et al 2004;Tasso et al 2009), green algae (Callow et al 2000;Pettitt et al 2004;Tasso et al 2009), bryozoans (Dobretsov et al 2007), and barnacles (Pettitt et al 2004;Aldred et al 2008;Tasso et al 2012). Several enzymes and enzyme blends can also cause oxidative damage through oxidoreductase-produced reactive oxygen species (eg hydrogen peroxide and hypohalogenic acids), which inhibit the formation of biofilms or degrade/remove biofilm matrices by hydrolyzing extracellular polymeric substances (Wiatr 1990;Johansen et al 1997;Leroy et al 2008;Friedrichs et al 2012).…”
Section: Inhibitors Of Adhesive Production/releasementioning
confidence: 99%